(untitled) (Bangladesh Agronomy Journal, 2021)
The experiment was carried out at the research field of the Department of Agronomy of Bangabandhu Sheikh Mujibur Rahman Agricultural University (BSMRAU), Gazipur during December 2016 to April 2017 to investigate the effect of different phosphorus levels (0, 30, 60 and 90 kg P ha-1) on the growth and yield of four selected cowpea genotypes (BARI Felon-1, A-06008, VI046192 and VI034386). The experiment was laid out in a factorial randomized complete block design with three replications. The results indicated that, among the genotype, BARI Felon-1 required minimum days to 1st (96 DAS) and 50% flowering (108 DAS) showing the highest absolute growth rate (0.71 g day-1), crop growth rate (23.69 g m-2 day-1), relative growth rate (0.047 g g-1 day-1), net assimilation rate (1.40 g m-2 day-1), leaf area index (6.68), SPAD value (51.03), seed length (0.71 cm) and breadth (0.54 cm). But the genotype, A-06008 gave the highest grain yield (0.62 t ha-1). Application of phosphorus at 90 kg ha-1 showed the highest leaf area index (6.67), SPAD value (50.98), pod length (14.33 cm), seed length (0.70 cm), seed breadth (0.50 cm) and grain yield (0.34 t ha-1). In terms of growth and yield, the cowpea genotype A-06008 showed the best performance at the phosphorus level of 90 kg ha-1. Bangladesh Agron. J. 2021, 24(1): 25-36